Level of waste management efficiency in the local government unit as perceived by the residents of Dolores, Eastern Samar. - Ayad, Veana Marie B. (Tacloban City Veana B. Marie Ayad [and] Kyrl Joyce B. Brozas, 2010)
Dolores is a third class municipality in the Province of Eastern Samar. Due to the continuing increase of its population, the waste generated in the municipality also increases. In line with this, it can be observed that there is no proper waste management in the municipality. Hence, it is for this reason that the researchers become interested in studying waste management efficiency in the Local Government Unit. This study is a descriptive-correlational research. It sought to determine the perception of the residents on the level of waste management efficiency in the Local Government Unit and how it is influenced by their demographic characteristics.
This research was conducted in the municipality of Dolores, Eastern Samar. The respondents of this study were determined using multi-stage sampling. There were 115 respondents in the study.
The levels of waste management efficiency were expressed through arithmetic means. And the relationships between variables were measured using eta, point biserial, and r-value. P-value was also used to determine whether the relationship between the variables is significant or not.
The results reveal that majority of the respondents are female, aged between 41-50 years old, married and obtained high school education. Overall there is an average perception of the residents on the level of waste management efficiency in the Local Government Unit. The results also showed that there is no significant relationship between the residents' demographic characteristics and their perception on the level of waste management in the LGU. This suggests that the perception of the residents on the level of waste management efficiency will be solely based with the performance and efficiency in the LGU regarding waste management and will not be influenced by their age, sex, civil status and highest educational attainment.
The findings of the study is important because this can help the Local Government in improving and developing waste management programs and policies with the aid of the residents' perception. This also will enhance environmental governance of the Local Government.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science